A novel mutation in the P2Y12 receptor and a function‐reducing polymorphism in protease‐activated receptor 1 in a patient with chronic bleeding. (May 2014) - Patel, Y. M.; Lordkipanidzé, M.; Lowe, G. C.; Nisar, S. P.; Garner, K.; Stockley, J.; Daly, M. E.; Mitchell, M.; Watson, S. P.; Austin, S. K.; Mundell, S. J.
Summary Background The study of patients with bleeding problems is a powerful approach in determining the function and regulation of important proteins in human platelets. We have identified a patient with a chronic bleeding disorder expressing a homozygous P2RY12 mutation, predicting an arginine to cysteine (R122C) substitution in the G‐protein‐coupled P2Y12 receptor. This mutation is found within the DRY motif, which is a highly conserved region in G‐protein‐coupled receptors (GPCRs) that is speculated to play a critical role in regulating receptor conformational states. Objectives To determine the functional consequences of the R122C substitution for P2Y12 function. Patient/methods We performed a detailed phenotypic analysis of an index case and affected family members. An analysis of the variant R122C P2Y12 stably expressed in cells was also performed. Results ADP‐stimulated platelet aggregation was reduced as a result of a significant impairment of P2Y12 activity in the patient and family members. Cell surface R122C P2Y12 expression was reduced both in cell lines and in platelets; in cell lines, this was as a consequence of agonist‐independent internalization followed by subsequent receptor trafficking to lysosomes. Strikingly, members of this family also showed reduced thrombin‐induced platelet activation, owing to an intronic polymorphism in the F2R gene, which encodes protease‐activated receptor 1 (PAR‐1), that has been shown to be associated with reduced PAR‐1 receptor activity. Conclusions Our study is the first to demonstrate a patient with deficits in two stimulatory GPCR pathways that regulate platelet activity, further indicating that bleeding disorders constitute a complex trait.